Acute lymphoblastic leukemia as second primary tumor in a patient with retinoblastoma - Anasua Ganguly; Swathi Kaliki; Faraz Ali Mohammad; Dilip K Mishra; S Vanajakshi; Vijay Anand Reddy (Oman Journal of Ophthalmology, 2016)
Second primary tumor (SPT) is defined as a second tumor that presents either simultaneously or after the diagnosis of an index tumor. Second primary malignancies are the leading cause of death in patients with heritable retinoblastoma (RB). Acute lymphoblastic leukemia (ALL), as SPT in RB patients, is extremely rare. To the best of our knowledge, only five cases of ALL as SPT in patients with RB has been documented in the literature. Herein, we report a case of a 6-year-old girl with bilateral RB, who developed ALL during the course of treatment of RB. This case highlights the importance of reviewing blood investigations regularly to diagnose leukemia as SPT in RB and also the necessity for proper counseling and lifelong follow-up in these patients.